Birdwatching atau Pengamatan Burung Sebagai Potensi Wisata Minat Khusus di Desa Gowong, Kecamatan Bruno, Kabupaten Purworejo - Dwi Sendi Priyono; Rahayu, Kinanthi (Direktorat Pengabdian kepada Masyarakat, 2023)
This article aims to collect data on bird species in Gowong Village. Data collection was carried out by exploring places that birds could potentially encounter. Then track the path and mark the observation points to be processed into an infographic map. With this activity, it is hoped that it can develop special interest eco-tourism in Gowong Village. Observations were made for 4 days in the form of plantations, rice fields, dry fields, rivers and community forests. The results obtained were 15 species of birds found in Gowong Village. Among them are Javanese Bondol, Cekakak Sungai, Cekakak Jawa, Sepah Kecil, Coconut Honeybird, Sriganti Honeybird, Cipoh Kacat, Black Kedasi, Gray Bentet, Bido Snake Eagle, Gemak Loreng, Hornbill, Cinenen Pisang, Cucak Kutilang, and Cabai Bunga Api. Based on these results, Gowong Village has the potential to be developed into a special interest tourist attraction, especially bird watching.